2014
DOI: 10.4028/www.scientific.net/amm.525.355
|View full text |Cite
|
Sign up to set email alerts
|

Study on Development Path of Electric Vehicle in China from a View of Energy Conservation and Emission Reduction

Abstract: In this paper, the change of fossil energy consumption, carbon dioxide (CO2) and pollutant emissions are calculated when petroleum based vehicles (PBVs) are taken place by EVs based upon the full-cycle energy efficiency theory with the energy efficiency measured from well to wheel.. Calculation results show that the fossil energy consumption, CO2, monoxide (CO) and hydrocarbon (HC) emissions can be reduced with the substitution of EVs for vehicles that burn gasoline (GVs), but nitrogen oxides (NOx) and sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Their lack of air pollutants and CO 2 emissions during the use phase make battery electric vehicles (BEVs) one of the most straightforward and effective means for the reduction in ambient air pollutants and CO 2 in the transportation sector [4,5]. While several studies have highlighted the synergistic effects of the emission mitigation of air pollutants and greenhouse gas (GHG) from the promotion of BEVs in China using a life cycle impact assessment approach [4][5][6][7], some researchers have indicated that there might be an increase in the emissions of air pollutants when considering the whole life cycle [8][9][10], or even an increase in CO 2 emissions [11]. Hence, it is meaningful to conduct a study on the fuel cycle in order to analyze the emission characteristics of BECVs, since most emissions from BECVs are produced from the power production stage in the fuel cycle indirectly [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Their lack of air pollutants and CO 2 emissions during the use phase make battery electric vehicles (BEVs) one of the most straightforward and effective means for the reduction in ambient air pollutants and CO 2 in the transportation sector [4,5]. While several studies have highlighted the synergistic effects of the emission mitigation of air pollutants and greenhouse gas (GHG) from the promotion of BEVs in China using a life cycle impact assessment approach [4][5][6][7], some researchers have indicated that there might be an increase in the emissions of air pollutants when considering the whole life cycle [8][9][10], or even an increase in CO 2 emissions [11]. Hence, it is meaningful to conduct a study on the fuel cycle in order to analyze the emission characteristics of BECVs, since most emissions from BECVs are produced from the power production stage in the fuel cycle indirectly [12][13][14].…”
Section: Introductionmentioning
confidence: 99%